Asymmetric effects of a modelled tidal turbine on the flow and seabed. (October 2020) - Ramírez-Mendoza, R.; Murdoch, L.; Jordan, L.B.; Amoudry, L.O.; McLelland, S.; Cooke, R.D.; Thorne, P.; Simmons, S.M.; Parsons, D.; Vezza, M.
Abstract: The extraction of power from the flow of water has become an important potential source of clean energy. In spite of significant interest in the interaction between energy extraction devices and water currents, comparatively little work has focused on flow asymmetry. Indeed, unusual wake behaviour and limits of turbine array efficiency have typically been attributed to boundary effects rather than the particular turbine geometry. The aim of the present study was to reveal the asymmetries in the hydrodynamic wake and the interactions with the sediment bed due to the presence of a hydrokinetic turbine. We combined: (i) computational fluid dynamics simulations; (ii) optical flow measurements from a series of flume experiments above a fixed rough bed; and (iii) acoustic measurements from a further series of flume experiments above a mobile sand bed. Results showed flow asymmetry due to the presence of the rotor which appeared to be related to the development of the wake and potentially to the gyre of the blades. Suspended sediments in the flume also exhibited asymmetrical characteristics due to the flow asymmetry. This imbalance in the flow field and sediment transport may decrease energy extraction efficiency in turbine arrays and also could have important environmental consequences. Highlights: Flow asymmetries and their effects on the sea bed were investigated. Near bed flow cross-stream differences were clearly seen far from the turbine. Sediment scour and deposition showed a non-uniform morphology at each side of the wake.